Kje prebivajo in delujejo kulturni ustvarjalci? - Kozina, Jani (Družboslovne razprave, 2018)
The article aims to examine the dynamics of the spatial distribution of cultural workers at various spatial scales in Slovenia. The dispersion of cultural workers is studied using a quantitative analysis of their place of residence and work. The results show the level of cultural agglomeration at the regional scale corresponds proportionally to the level of regional development, while there is greater concentration at the local level in more urban settlements. Surprisingly, there has been a spatial expansion and dispersion of cultural workers in recent years. In addition to the economy and real-estate prices, reasons for this may include the income inequality of cultural workers, the non-urban character of the Slovenian way of life and the specific spatial structure with good accessibility and mostly smaller settlement types.
Keywords: geografija; kulturne dejavnosti; kulturni prostori; Slovenija; umetniki; ustvarjalne dejavnosti; ustvarjalnost